THE EFFECT OF EXERCISE SCHEDULING (TOTAL AND PARTIAL) ON LEARNING-THE TECHNICAL PERFORMANCE OF THE TRIPLE JUMP EFFECTIVENESS FOR STUDENTS - Ali Abdullah Ahmed Al-Jubouri; Asst. Prof. Murad A. Yas Al-Jubouri (Proximus Journal Publishing, 2024)
The researcher used the experimental method to suit the nature of the research, and the research community was deliberately selected from the students of the second stage of study at the College of Physical Education and Sports Sciences at the University of Kirkuk for the academic year 2024/2023, which numbered (83) students, while the research sample was randomly selected and numbered (30) students, distributed to two experimental groups (14) students for each group, and the educational programs for the two experimental groups were implemented, as the first experimental group was implemented (scheduling the total exercise) and the second experimental group was implemented (scheduling). partial exercise), and the data were processed by a number of appropriate statistical means
Keywords: number; Exercise scheduling; total style; technical performance